Topical Steroids: Awareness and Misuse Among General Medical Practitioners - Hali, F.; Zakaryaa, S.; Chiheb, S. (British Journal of Healthcare and Medical Research, 2023)
Introduction: Topical steroids (TS) contributed in the management of several inflammatory, tumoral or allergic dermatoses. However, their misuse may lead to serious or even irreversible adverse effects. This study aimed to evaluate the knowledge and attitudes of general medical practitioners in Morocco regarding topical steroids use and misuse. Materials and Methods: Cross-sectional national survey over a 4-month period from 01/09/2022 to 30/12/2022. The data was collected by a Google Forms questionnaire which was shared on different professional groups on the social networks. The target population was Moroccan general practitioners. Data analysis was performed by Excel software. Results: A total of 200 general medical practitioners answered the questionnaire, of which 133(66.5%) practiced in the public sector and 67(33.5%) in the private sector. 11% had rated their frequency of prescription as high, 56% as medium and 33% as minimal or rare; the indications were dominated by eczema, atopic dermatitis and psoriasis. The prescription of topical corticosteroids started from the age of 1 year in 32.5% of general practitioners while the majority prescribed them at any age. Sixty (30%) were aware of the pharmacological effects of topical corticosteroids. The most frequently prescribed galenic form was cream in 95% of cases followed by gels, lotions and finally preparations. One hundred and thirty-three (66%) had answered correctly to the indications of topical corticosteroids and 106(53%) prescribed them in short cures. Few doctors (1%) had been able to identify all side effects. One hundred and fifty (75%) of the general medical practitioners had already seen patients presenting adverse effects dominated by skin atrophy, delayed healing, depigmentation, fungal or bacterial infection; their response consisted of degression in 75% of cases or switching to a lower class, while 11.5% had wrongly suggested an abrupt discontinuation. Conclusion: The high frequency of topical steroids side effects is an increasing problem encountered by dermatologists. Lack of some general practitioners and patient awareness are also important underlying factors. To our knowledge, this is the first Moroccan study that aimed to evaluate the knowledge, attitudes, and behavior regarding topical corticosteroids by general medical practitioners.